2017
DOI: 10.1210/js.2017-00278
|View full text |Cite|
|
Sign up to set email alerts
|

Coxsackievirus-Induced Proteomic Alterations in Primary Human Islets Provide Insights for the Etiology of Diabetes

Abstract: Enteroviral infections have been associated with the development of type 1 diabetes (T1D), a chronic inflammatory disease characterized by autoimmune destruction of insulin-producing pancreatic beta cells. Cultured human islets, including the insulin-producing beta cells, can be infected with coxsackievirus B4 (CVB4) and thus are useful for understanding cellular responses to infection. We performed quantitative mass spectrometry analysis on cultured primary human islets infected with CVB4 to identify molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…Cells were also collected at 24, 48, and 72 h for total RNA and protein. Primary human islets were plated and infected as previously described [12], with cells being collected at 72 h for protein.…”
Section: Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells were also collected at 24, 48, and 72 h for total RNA and protein. Primary human islets were plated and infected as previously described [12], with cells being collected at 72 h for protein.…”
Section: Infectionmentioning
confidence: 99%
“…Samples were processed as previously described [12]. In brief, SC-β cells were harvested and washed three times with PBS prior to processing for mass spectrometry.…”
Section: Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we treated EndoC-βH1 cells with polyinosinic-polycytidylic acid (PolyI:C). PolyI:C is a synthetic dsRNA recognized in the cytoplasm by dsRNA pattern recognition receptors (PRRs) that mimics, at least in part, the effects of viral infection on β cells (16,17). We demonstrated that human β cells dedifferentiate following PolyI:C treatment and enteroviral infection.…”
Section: Introductionmentioning
confidence: 99%